Analysis of The Ina219 Sensor System And Voltage Divider On A Calibrate Multimeter: Fitri Puspasari, Trias Prima Satya - Fitri Puspasari Fitri Puspasari; Trias Prima Satya Trias Prima Satya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2024)
Research has been carried out on uncertainty studies in current and voltage measurements based on the Internet of Things using the NodeMCU ESP8266 microcontroller. This research aims to design a current and voltage or power meter using a current sensor in the form of an INA219 module and a voltage sensor with a microcontroller-based voltage divider circuit module and determine the validity of the measuring results of the instrument created. The method used in this research consists of three stages: hardware design, software design and system testing.